2022
DOI: 10.37748/2686-9039-2022-3-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pathophysiology of tumor growth and functional activity of the hypothalamic-pituitary-thyroid axis in rats of both sexes with the development of Guerin's carcinoma on the background of hypothyroidism

Abstract: Purpose of the study. Was to analyze changes in pathophysiological parameters of transplantable tumor growth and functional activity of the hypothalamic-pituitary-thyroid axis (HPT) in rats of both sexes with Guerin's carcinoma in presence of induced hypothyroidism.Materials and methods. The dynamics of tumor growth and average life span were assessed in white alley rats of both sexes with Guerins carcinoma transplanted subcutaneously on the background of thyreostatic induced hypothyroidism. RIA (radioimmune a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Previously, we found that induced hypothyroidism inhibited the growth of transplanted Guerin's carcinoma and increased life expectancy only in female rats, while in male rats, despite the fact that the size of the tumors was smaller at the initial stages, after 2 weeks of the experiment it was comparable with the parameters in the animals with the independent tumor growth, and no increase in life expectancy was observed [16,17]. An analysis of the content of hypothalamic Gn-releasing and pituitary tropic hormones LH, FSH and prolactin (PRL) in rats of both sexes is presented in Table 1 herein.…”
Section: Resultsmentioning
confidence: 84%
“…Previously, we found that induced hypothyroidism inhibited the growth of transplanted Guerin's carcinoma and increased life expectancy only in female rats, while in male rats, despite the fact that the size of the tumors was smaller at the initial stages, after 2 weeks of the experiment it was comparable with the parameters in the animals with the independent tumor growth, and no increase in life expectancy was observed [16,17]. An analysis of the content of hypothalamic Gn-releasing and pituitary tropic hormones LH, FSH and prolactin (PRL) in rats of both sexes is presented in Table 1 herein.…”
Section: Resultsmentioning
confidence: 84%
“…Previously, we found that in female rats, hypothyroidism slowed down the increase in the volume of primary tumors of Guerin's carcinoma and prolonged their life expectancy. In males, a slight slowdown in the tumor growth was noted only up to day 14 after inoculation, then the tumor grew rapidly, and its volume did not differ from that recorded in the reference group, and no increase in life expectancy was reported [9,10]. It was just during that period, upon expiration of 19 days of the tumor growth, when significant gender differences in the growth of Guerin's carcinoma were revealed by us, and studies of indicators in blood and tissues were carried out.…”
Section: Resultsmentioning
confidence: 93%
“…It is known that the growth of a malignant tumor has a significant and often sex-dependent effect on the body's regulatory axes [9]. Moreover we previously found that induced hypothyroidism had an inhibitory effect on the growth of Guerin's carcinoma and S45 sarcoma only in the females, but not in the males [10,11].…”
Section: Introductionmentioning
confidence: 79%